Methodology of Teaching Language: Current Approaches, Innovations, and Pedagogical Strategies (Journal of Pedagogical Inventions and Practices, 2024)
This scientific article delves into the dynamic landscape of language teaching methodology, examining contemporary approaches, innovative techniques, and effective pedagogical strategies. Focused on methodologies such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), technology-enhanced language learning, and learner-centered approaches, the study synthesizes current research findings and educational practices. The aim is to offer insights into the evolving field of language instruction, exploring the effectiveness, adaptability, and impact of these methodologies on language acquisition. Through a comparative analysis and synthesis, the article provides educators and researchers with valuable guidance on selecting and integrating methodologies to enhance language education in diverse contexts. The conclusion outlines potential future directions, emphasizing emerging trends and the importance of continued research in shaping effective language teaching practices.